Relación entre las transferencias de los recursos ordinarios y el crecimiento económico en la región Loreto en el periodo 2018 – 2022 - Arias Alvan, Andrea Marina (2024)
The purpose of this research was to examine the relationship between transfers of ordinary resources and economic growth in the Loreto region during the period between 2018 and 2022. To achieve this objective, a correlational study was carried out with a non-experimental design, analyzing the behavior of transfers for ordinary resources (considered independent variables) and the evolution of the region's economic growth, measured through the Gross Domestic Product (GDP) as a dependent variable. The results obtained revealed a considerable positive correlation, reflected in a correlation coefficient (r) with a value of r = 0.00141421356, indicating that an increase in one of the variables is associated with an increase in the other. On the other hand, income from ordinary resources showed a variable behavior with a clearly increasing trend, starting at S/ 1,431,867,587.00 in 2018 and reaching S/ 1,900,967,147.00 in 2022. As for GDP, it experienced variations with an average growth of 2.27%.